E-Government and Digital Service Delivery: Investigating the Adoption of Digital Platforms for the Purpose of Citizens' Service Access, Transparency Increase, and Administrative Efficiency Promotion - Abdillahi, Mustafe Mahamoud (Generasi Sains Indonesia, 2026)
This study examines the adoption of digital platforms in e-government and their implications for citizen access, transparency, and administrative efficiency. Using a systematic literature review approach, the study analyzes 92 peer-reviewed articles indexed in Scopus and Web of Science, applying a PRISMA-based selection process and thematic analysis. The findings identify three main dimensions influencing digital platform adoption: drivers, barriers, and outcomes. Key drivers include citizen expectations, organizational efficiency, technological advancements, and regulatory frameworks, while major barriers consist of digital divide, institutional constraints, fragmented regulations, and trust issues. The results demonstrate that digital platforms improve service access, enhance transparency, and increase efficiency; however, these benefits are uneven and often constrained by structural and institutional limitations. The study further reveals the presence of an “access paradox,” “opaque transparency,” and “islands of automation,” indicating gaps between technological potential and practical implementation. A conceptual framework is proposed to illustrate the dynamic interaction between drivers, barriers, and outcomes. This study contributes to the literature by providing a multi-level analytical perspective and offers insights for policymakers to design more inclusive, integrated, and context-sensitive digital governance strategies.